ChemInform Abstract: Highly Stereoselective aza‐Baylis—Hillman Reactions of CF3‐Sulfinylimines: Straightforward Access to α‐Methylene β‐CF3 β‐Amino Acids. Issue 5 (February 2015) - Milcent, Thierry; Hao, Jing; Kawada, Kosuke; Soloshonok, Vadim A.; Ongeri, Sandrine; Crousse, Benoit
Abstract The tert‐butanesulfinyl group acts as chiral auxiliary and is removed after the aza‐Baylis—Hillman reaction in the presence of HCl in dioxane.